(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: To evaluate burnout among Nurses at Hospitals in Nasiriyah City, Methodology: The sample of the study was purposeful and included (216) nurses, who were selected from hospitals from October 2, 2016, to June 28, 2017 CE. Results: The study’s results have showed (63.9%) of the sample were (19 - 28) years, (74.1%) of the sample have experience of year (<10), (41.7%) were preparatory, (95.8%) of the sample were Urban, (47.2%) of the sample were Sometime enough of Economic status, the results have revealed that there is a moderate assessment in for an overall satisfied related to job satisfaction (128, 59.3%). Recommendations: The study recommends an Establish laws that protect nurses from abuse and stress at work. Commitment by the ethics of the profession and work according to the policy of the institution